Numenius arquata (Charadriiformes, Aves) abundance trends in agrolandscapes in the southern Republic of Karelia (Northwest Russia) - Sergey A. Simonov; Alexander V. Artemyev; Nikolay V. Lapshin; Andrey O. Tolstoguzov; Maria V. Matantseva (Nature Conservation Research: Заповедная наука, 2024)
Olonets grasslands (61.041111° N, 32.931389° E) are the most extensive agrolandscapes in the Republic of Karelia (Northwest Russia), one of the largest spring stopovers of migrating birds in Northern Europe and a breeding area of farmland-associated birds. This territory is essential for the life of many bird species and is listed among international-level Important Bird and Biodiversity Areas of Russia. However, the preservation level of Olonets grasslands is rather low, since only spring hunting has been prohibited in a part of the Olonets grasslands (49 km2) since 1993. Thus, the conservation status of this area and the bird protection measures have to be upgraded and a system should be set up for monitoring the abundance of Red Data Book and other threatened species, which use this territory in certain stages of their life cycle. One of such species is Numenius arquata (hereinafter – curlew), many populations of which have both declining abundance and shrinking distribution. This species uses the Olonets grasslands both as a spring migration stopover and as a breeding area. We analysed the curlew registrations obtained in the Olonets grasslands in April and May 1997–2023 during the transect censuses (both transect walks and surveys using a car). We compared these records with both local weather data and grassland use intensity. We also analysed the time dependence of curlew spring abundance on date and year of observations. The research hypothesis was that curlew's abundance decreased in cold spring seasons, in seasons with intensive grassland use, as well as over time. The latter supposition is based on the observations of a curlew population decline in the past decades in various parts of the species' range. The monitoring showed that this species is consistently present in the Olonets grasslands in April – May. Curlews, stopping over on migration, used the grasslands quite evenly, with no clear preference for any specific areas. In the case of breeding, however, they tended to choose the sites most inconvenient for agricultural treatments. The even distribution of curlews over the grasslands was probably due mostly to the individuals foraging in stopovers. In the surveyed part of the Olonets grasslands (49 km2), the size of the local population breeding varied from 30 to 150 pairs in 1999–2023. In 2019–2023, it was 30–90 pairs. In the entire Olonets grasslands (180 km2), the breeding curlew population varied from 100 to 1200 pairs at various years in 1999–2023, but it did not exceed 100–300 pairs in 2019–2023. During the stopping over on migration, the annual number of curlew individuals passing through the surveyed part of the Olonets grasslands was 90–750, while it was 150–2500 birds in the entire Olonets grasslands. So far, we have found no correlation between the total abundance of curlews in the study area and the intensity of grassland use, apparently because stopover and breeding sites are still available. On the other hand, the curlew abundance was lower in warmer spring seasons. Apparently, some curlews fly farther north in such seasons, whereas in colder seasons more birds settle on Olonets grasslands or linger on them on their migration route. Over 25-year retrospective, the total curlew abundance registered in the Olonets grasslands has decreased by 34.4%. In the study area, the negative trend in the species abundance was likely due not only to local but also to global processes, which have caused a decline in some other European populations as well. These birds probably face with certain problems on flyways or in wintering grounds, but more data are needed to verify this conjecture. The local-scope factors that may potentially affect curlew abundance include burning of last year's grass cover, farming intensification, predation, and human disturbance. By assessing possible future changes in the curlew abundance in the Olonets grasslands, we predict that in the coming 30–40 years this species is highly likely to become «endangered» in the study area. To prevent this from happening, it is necessary to conserve the sites where curlews can nest, strengthen the protection regime in the Olonets grasslands (preferably through designation of a high-status Protected Area), and raise public awareness of the need to conserve the species and reduce human disturbance.